Evaluation of acoustic and physical properties of composite boards from sugarcane bagasse and oil palm waste - Sunardi, Sunardi; Wahyudi, Riyanto; Ula, Shofiatul; Haryadi, Haryadi; Alhamidi, Ahmad Ali (Politeknik Negeri Lhokseumawe, 2025)
Sugarcane bagasse and oil palm Empty Fruit Bunches (EFB) are abundant agricultural by-products in Indonesia that, if unmanaged, pose significant environmental risks. This research investigates their potential as sustainable raw materials for composite acoustic boards. Composites were fabricated using hybrid fibers consisting of 67% bagasse and 3% EFB, bonded with a matrix of Polyvinyl Acetate (PVAc) and varying ratios of epoxy resin (0%, 1%, 2%, and 4%). Boards were cold-pressed at 20 MPa for 30 minutes and air-dried for 7 days. The incorporation of epoxy resin significantly improved physical integrity and acoustic performance. Sound Absorption Coefficients (SAC) increased from 0.37 (0% epoxy) to 0.67 (4% epoxy), indicating enhanced absorption in mid-to-high frequency ranges. These results support the feasibility of utilizing agricultural waste for sustainable engineering applications, thereby contributing to the development of eco-friendly materials.